2022
DOI: 10.1681/asn.2021060751
|View full text |Cite
|
Sign up to set email alerts
|

Serum Protein Exposure Activates a Core Regulatory Program Driving Human Proximal Tubule Injury

Abstract: Background: The kidneys efficiently filter waste products while retaining serum proteins in the circulation. However, numerous diseases compromise this barrier function, resulting in spillage of serum proteins into the urine (proteinuria). Some studies of glomerular filtration suggest that tubules may be physiologically exposed to nephrotic-range protein levels. Therefore, whether serum components can directly injure the downstream tubular portions of the kidney, which in turn can lead to inflammation and fibr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 118 publications
1
12
0
Order By: Relevance
“…By analyzing TF regulatory networks, we identify RXRα as a key regulator in modulating accessible chromatin during adaptive repair. Consistent with our study, Lidberg et al recently showed that RXRα motifs are enriched in open chromatin regions in normal human kidney cortex, but are diminished after injury 29 . Indeed, bexarotene-induced activation of RXRα restores chromatin states, reprograms gene expression, and protects TECs from severe injury.…”
Section: Discussionsupporting
confidence: 93%
“…By analyzing TF regulatory networks, we identify RXRα as a key regulator in modulating accessible chromatin during adaptive repair. Consistent with our study, Lidberg et al recently showed that RXRα motifs are enriched in open chromatin regions in normal human kidney cortex, but are diminished after injury 29 . Indeed, bexarotene-induced activation of RXRα restores chromatin states, reprograms gene expression, and protects TECs from severe injury.…”
Section: Discussionsupporting
confidence: 93%
“…We thank Dr. O'Neill for his interest in our recent study, 1 which showed that serum components other than albumin drive a proinflammatory response in proximal tubule epithelial cells (PTECs) in vitro-a finding that was supported by observations in a preclinical model of renal fibrosis and in patients with proteinuric kidney disease. In his letter, Dr. O'Neill points out an important difference in the composition of serum versus plasma-namely, that clotting of blood to generate serum can increase the levels of certain soluble factors due to platelet activation such as chemokines, cytokines, and growth factors, which may have a confounding effect on our interpretation of a proinflammatory tubular response to serum.…”
Section: Authors' Reply: Serum Proteininduced Tubular Injurymentioning
confidence: 85%
“…Lidberg et al 1 demonstrate that human serum, but not albumin, elicits changes in human proximal tubular cells in culture and propose that proteins other than albumin are responsible for tubular damage in some types of nephrotic syndrome. However, serum is derived from the clotting of blood and, therefore, contains a host of compounds released from platelets, including cytokines, other inflammatory mediators, and growth factors (not all of which are proteins), that are not normally present or are present at much lower levels in circulating blood.…”
mentioning
confidence: 99%
“…We have previously generated chromatin accessibility (ATAC-seq) and conformation data (Hi-C) to identify the regulatory control mechanisms of cultured kidney cells 31 . While useful, in vitro culture can induce injury responses in cells 32 , and therefore characterization of intact tissues with minimal manipulation is essential to understand their baseline epigenomic landscapes. Here we present reference-quality functional genomic datasets for human kidney cortex and medulla that will provide a valuable resource for kidney investigators.…”
Section: Discussionmentioning
confidence: 99%